Assessing forest biomass and diversity of tree populations in Tekam Forest Reserve, Pahang, Malaysia - HASYA HANNANI RUZIMAN; AZIAN MOHTI; NIK NORAFIDA BINTI NEK ALI @ NIK ALI; ASMIDA ISMAIL; FAEAH PARDI (Society for Indonesian Biodiversity, 2024)
Abstract. Ruziman HH, Mohti A, Nik Ali NNBNA, Ismail A, Pardi F. 2024. Assessing forest biomass and diversity of tree populations in Tekam Forest Reserve, Pahang, Malaysia. Biodiversitas 25: 2821-2827. Free Air CO2 Enrichment (FACE) experiments are long-term monitoring projects to comprehend the response of forest ecosystems to future atmospheres with CO2 enriched. Therefore, the research aims to determine the forest biomass and species diversity in the FACE system of Tekam Forest Reserve (TFR), Pahang, Malaysia. The sampling plots of 25 m × 20 m were established in TekamFACE as experimental plot and control plot in TFR. Allometric equation, Shannon-Wiener, and Evenness indices were used to estimate the standing biomass, carbon stock and species diversity, respectively. Tekam FACE system recorded total forest biomass of 54.38 ton/ha, contributed by 42.82 tons/ha of Above-Ground Biomass (AGB) and 11.56 tons/ha of Below-Ground Biomass (BGB). High carbon stock was also estimated at both forest plots with 27.19 tons/ha in TekamFACE and 17.35 tons/ha in control plot. These values indicated that the forest has high biomass, which can contribute to carbon sequestration that help mitigate the impacts of climate change. Further, this forest recorded high Species Diversity (H’) and Species Evenness (E) at TekamFACE (H’ = 4.04; E = 0.93) and control plot (H’ = 3.53; E = 0.83). Overall, this research emphasized that forests with rich biodiversity have substantial carbon sequestration capacity for the adaptation of forest ecosystems to future atmospheric changes.